Measurement and modeling diffusivities of bioactive compounds in compressed liquids - Silva, José Miguel Cardoso da (2020)
Over the last decade, the growing concern about global health, treatment and disease prevention has led to a rapid expansion of the market of bioactive compounds, which induced the pharmaceutical, cosmetics and food industries to invest in the extraction and recovery of such molecules. The global market for bioactive compounds has exceeded 27 billion dollars by 2015 and it is estimated to reach 51.71 billion dollars by 2024. Many industrial separations, such as solid-liquid and supercritical extractions, are often limited by mass transfer phenomena, and thus there is a great need to know diffusion coefficients in order to model, design and optimize these processes properly. In this sense, the main objective of this dissertation was the measurement and modeling of diffusion coefficients of two bioactive compounds of interest, namely, lycopene in ethanol and astaxanthin in ethyl acetate. To perform the diffusivity measurements at infinite dilution, it was used the chromatographic peak broadening (CPB) method, in the temperature range of 303.15 to 333.15 K and pressure range of 1 to 100 bar. The diffusivity values obtained are between 3.447×10-6 and 6.679×10-6 cm2 s-1 for lycopene and between 8.172×10-6 and 1.223×10-5 cm2 s-1 for astaxanthin. Subsequently, the measured diffusivities were analyzed as a function of their dependence on temperature, pressure, solvent density, and in Stokes-Einstein coordinates. Finally, the results were modeled using several models from the literature, The calculated and experimental diffusion coefficients were compared based on the average absolute relative deviation (AARD). The values exhibit deviations varying between 5.00 and 91.29 % for lycopene and 3.94 and 79.38 % for astaxanthin. For both compounds it was verified that the empirical and semi-empirical equations of Magalhães et al., with deviations of 5.00 to 8.92 % and 3.94 to 7.29 % (for lycopene and astaxanthin, respectively), the free volume model of Dymond-Hildebrand-Batchinsky (DHB) with deviations of 9.78 and 4.80 % (for lycopene and astaxanthin, respectively) and the hybrid 1-parameter Tracer Liu-Silva-Macedo correlation (TLSMd), with deviations of 6.92 and 6.37 % (for lycopene and astaxanthin, respectively) are most suitable to describe the diffusivity of the studied compounds